An Analysis of Multi-objective Fuzzy Stochastic Nonlinear Programming Models - Beaula, Thangaraj; Seetha, R. (Communications in Mathematics and Applications, 2022)
A novel method is developed for multi-objective fuzzy stochastic nonlinear programming models with some stochastic constraints in which randomness is described by gamma random variables and fuzziness is expressed by L-R fuzzy numbers. The solution for aforesaid model is obtained by three stages: Defuzzification, conversion of MOSNLPP into MONLLP using chance constrained technique and solving multi objective deterministic nonlinear programming problem. An example is exemplified to validate and strengthen the efficacy of proposed technique.
Keywords: Multi objective fuzzy stochastic nonlinear programming; L-R fuzzy numbers; Gamma distribution